Intron-Mediated Enhancement of Gene Expression Independent of Unique Intron Sequences and Splicing - Rose, Alan B. (American Society of Plant Physiologists, 2000)
Either of the first two introns of the Arabidopsis tryptophan pathway gene PAT1 elevates mRNA accumulation from a PAT1:β-glucuronidase (GUS) fusion roughly 5-fold without affecting the rate of PAT1:GUS transcription. To further explore the mechanism of this intron-mediated enhancement of gene expression, we wanted to determine whether splicing or specific intron sequences were necessary. In-frame derivatives of PAT1 intron 1, whose splicing was prevented by a point mutation or large deletions, were able to increase mRNA accumulation from a PAT1:GUS fusion, demonstrating that splicing per se is not required. Furthermore, each of a series of introns containing overlapping deletions that together span PAT1 intron 1 increased PAT1:GUS mRNA accumulation as much as the full-length intron did, indicating that all intron sequences are individually dispensable for this phenomenon. These results eliminate the simple idea that this intron stimulates mRNA accumulation via a unique RNA-stabilizing sequence or through the completed act of splicing. However, they are consistent with a possible role for redundant intron sequence elements or an association of the pre-mRNA with the spliceosome.